2021
DOI: 10.1038/s41598-021-87754-2
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac MRI structural and functional predictors of left ventricular ejection fraction recovery following PVC catheter ablation

Abstract: Frequent premature ventricular contractions (PVCs) can induce cardiomyopathy (PVC CM). We sought to use cardiac magnetic resonance imaging (CMR) to quantify changes in cardiac structure and function of cardiomyopathy patients following catheter ablation for PVCs. Patients undergoing PVC ablation at the Johns Hopkins Hospital with pre-procedural CMR from 2010 to 2018 were included in this study. CMR Images were analyzed to collect information on cardiac structure and function as well as to quantify scar. Of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…Studies have found that a higher frequency of PVCs correlates to the severity of LV dysfunction [11,12,45]. However, it is important to note that cases with frequent PVCs do not necessarily have cardiomyopathy and it is thought that the duration of having PVC might also correlate to the development of PIC [11,44,46,47], making a clear cutpoint that assures the development of cardiomyopathy hard to estimate. Some authors have suggested 10,000-20,000 PVCs/day or PVCs > 10% of total beats as a high PVC burden [42].…”
Section: Diagnosismentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have found that a higher frequency of PVCs correlates to the severity of LV dysfunction [11,12,45]. However, it is important to note that cases with frequent PVCs do not necessarily have cardiomyopathy and it is thought that the duration of having PVC might also correlate to the development of PIC [11,44,46,47], making a clear cutpoint that assures the development of cardiomyopathy hard to estimate. Some authors have suggested 10,000-20,000 PVCs/day or PVCs > 10% of total beats as a high PVC burden [42].…”
Section: Diagnosismentioning
confidence: 99%
“…A study found that PVCs with RV origins are statistically correlated to persistently reduced EF even after ablation [47]. However, other studies showed only epicardial origins are correlated with the development of PIC and are associated with the highest risk of cardiomyopathy [30].…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…GLS appears to be useful to predict changes in LV function. Additionally, GLS is considered a prognostic indicator in PVICM, based on the association between mortality and GLS levels in cardiomyopathy patients [ 78 ].…”
Section: Examination Technology Of Pvicmmentioning
confidence: 99%